CROSS-MARKET IMPACT OF PLATFORMS' ACTIVITIES: A SECONDARY RELEVANT MARKET APPROACH. (13th April 2022) - Lee, Ki Jong
Abstract: As platform industries prosper, games are becoming more and more like a team competition rather than an individual sport. Literature on platform envelopment and ecosystems competition shed light on the increasing need to consider cross-market effects of platforms' activities in competitive analysis. Some established legal principles consider cross-market effects of platforms activities. However, they apply under strict conditions and may not be easily extended to cover the wide variety of platforms' activities. Thus, this article proposes to introduce a secondary relevant market approach, whereby courts and competition agencies should be obliged to define a secondary relevant market and consider pro- and anticompetitive factors in that market, which significantly affect competition in a primary (original) relevant market. By applying the approach, we could address the increasing need to consider cross-market effect of platforms' activities, without interrupting the keynote of traditional market definition, which focuses on close substitutes. It also enables us to fairly distribute the burden of proof among the parties. The approach can be applied in various contexts, such as platform market definition, nascent acquisition, platform envelopment, and ecosystems competition. It could also help legislators to pursue better targeted regulatory intervention.